2009
DOI: 10.1002/jmv.21419
|View full text |Cite
|
Sign up to set email alerts
|

Identification of mutations in a temperature‐sensitive mutant (tsm5) of murine cytomegalovirus using complementary genome sequencing

Abstract: Identification of mutations in mutants derived chemically is a difficult and relatively random process. NimbleGen Comparative Genome Sequencing (CGS) was assessed as an inexpensive, rapid method of identifying mutations in the temperature-sensitive mutant tsm5 of the K181 (Birmingham) variant of murine cytomegalovirus (MCMV). This genome resequencing approach requires an established genome sequence as a reference. Comparison of tsm5 and the K181 (Birmingham) variant with the published K181 (Perth) MCMV genomic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Thirty‐one mutations have now been identified in MCMV mutant tsm 5 [Timoshenko et al, 2009a, b], 18 of which result in an amino acid change and eight of the latter have so far been examined for their role in the temperature phenotypes of tsm 5. In a previous study, it was shown that the C to T mutation that leads to a tyrosine replacement of cysteine at amino acid residue 890 in the M70 (primase) gene, when introduced into the wt virus, made the virus temperature‐sensitive, as its growth was drastically reduced at 40°C.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirty‐one mutations have now been identified in MCMV mutant tsm 5 [Timoshenko et al, 2009a, b], 18 of which result in an amino acid change and eight of the latter have so far been examined for their role in the temperature phenotypes of tsm 5. In a previous study, it was shown that the C to T mutation that leads to a tyrosine replacement of cysteine at amino acid residue 890 in the M70 (primase) gene, when introduced into the wt virus, made the virus temperature‐sensitive, as its growth was drastically reduced at 40°C.…”
Section: Discussionmentioning
confidence: 99%
“…[Bevan et al, 1996]. Recently, using capillary and complementary genome sequencing to sequence the whole genome, a total of 13 synonymous and 18 non‐synonymous single nucleotide polymorphisms (SNPs) have been identified in tsm 5 [Timoshenko et al, 2009a, b]. Initial attempts to identify which mutations contribute to the ts phenotype of tsm 5 concentrated on mutations in genes involved in DNA replication, processing, and packaging as electron microscopy showed that tsm 5 had a defect in DNA encapsidation and that DNA synthesis was significantly reduced at 40°C.…”
Section: Introductionmentioning
confidence: 99%
“…NimbleGen Comparative Genome Sequencing (CGS) identified 10 synonymous and 15 non-synonymous SNPs in tsm5, and 14 of the latter were confirmed by conventional sequencing: m20 (2 SNPs), m21, M25, M34, M36, M47, M53, M70, M98, m132.1, m139, m141, m143 [16]. Two further SNPs (M27, M56) not identified by CGS were identified by sequencing, which also revealed that tsm5 was a mixture of mutants in that at least six loci (M27, M36, M53, M56, M70, M98) were polymorphic, although generally the mutant nucleotide was dominant.…”
Section: Studies With Murine Cytomegalovirus (Mcmv) Mutant Tsm5mentioning
confidence: 98%
“…Genome sequence provides important insights into the biology of medicinal mushroom R. griseocarnosa (F. Yu, Song, Liang, Wang and Lu, 2020 ). In addition, complementary genome sequencing has proved useful for identifying single-point mutations ( Timoshenko et al, 2009 ). Genome and transcriptome sequencing of P. portentosus was performed during the different growing stages, provide a new perspective for understanding the key pathways and hub genes involved in P. portentosus development ( Wan et al, 2021 ).…”
Section: Breeding Techniquesmentioning
confidence: 99%
“…Comparative transcriptomes of fruiting bodies of complex multicellular Agaricomycetes (mushroom-forming fungi) combine with comparisons of whole genomes conserved the developmental functions and complex multicellularity in fruiting bodies( Krizsan et al, 2019 ). Complementary Genome Sequencing has proved useful for identifying single-point mutations in a temperature-sensitive mutant, however CGS failed to recognize some SNPs and false positive SNPs were also identified out( Timoshenko et al, 2009 ).…”
Section: Breeding Techniquesmentioning
confidence: 99%